Kenji Mizoguchi cinematographic style (Long Take) in 'The Life of Oharu' (1952) - Rickmarthel, Julian Kayug (Universiti Malaysia Sarawak (UNIMAS), 2013)
This study aimed to identify and study the techniques of cinematography (long take) through the review of the film "The Life of Oharu" (1952) directed by Kenji Mizoguchi. Long Take is the technique of taking a shot with a long duration that is not the same with the usual techniques (Bordwell D. (2008)). However, the duration of the 'long take' video of film is different depending on the influence of a director. Methods of data collection through content analysis is used to identify data about long take duration and themes found in the films studied. Form the study, the researcher will produce a short video entitled 'Nexus'.